2008
DOI: 10.1016/j.brainres.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Vsx1 by its paralog Chx10/Vsx2 is conserved in the vertebrate retina

Abstract: Chx10-and Vsx1 are the only Paired-like CVC (Prd-L:CVC) homeobox genes in the mouse genome. Both are expressed in the retina and have important but distinct roles in retinal development. Mutations in Chx10 cause reduced retinal progenitor cell (RPC) proliferation and an absence of bipolar cells, while mutations in Vsx1 impair differentiation of cone bipolar cells. Given their structural similarities and importance in retinal development, we sought to determine if a regulatory interaction exists between these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 67 publications
8
78
1
Order By: Relevance
“…5e). This enrichment in the ChIP sample was even higher than the observed for a fragment of the vsx1_promoter, previously identified as a Vsx2 direct target 48 ( Fig. 5e).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…5e). This enrichment in the ChIP sample was even higher than the observed for a fragment of the vsx1_promoter, previously identified as a Vsx2 direct target 48 ( Fig. 5e).…”
Section: Resultsmentioning
confidence: 52%
“…A number of knockdown studies in zebrafish have shown that the reported role for Vsx2 in mammals is, at least, partially conserved in teleosts. Thus, small eye phenotypes, abnormal bipolar cell specification and Mitf upregulation have been described in vsx2-knockdown embryos in zebrafish 15,16,48 . Interestingly, one of these reports 15 described abnormally shaped eyes displaying a flattened morphology at early stages in zebrafish (24 h.p.f.).…”
Section: Discussionmentioning
confidence: 94%
“…18,[21][22][23][24][25][26][27] It is initially transcribed in a wide embryonic region but gradually restricted within distinct cell types at subsequent developmental stages. Therefore, post-transcriptional regulation might be required for the transition from one developmental stage to the next and the establishment of different cell identities.…”
Section: Discussionmentioning
confidence: 99%
“…18,23,24,26,27 To determine whether inhibition of Vsx1 expression by miR-20a is essential for normal embryogenesis, we examined whether releasing the inhibition by decoying miR-20a could elicit excessive generation of vsx1 marked neurons. Whole mount in situ hybridization showed that, at 18 hpf, wild type embryos generated 9 distinct vsx1 marked neurons in the central tier of spinal cord and the neurons were arranged in regular space corresponding to the somites ( Fig.…”
Section: Mir-20a Is Essential For Normal Embryogenesis By Preventing mentioning
confidence: 99%
See 1 more Smart Citation